The last assignment : a novel of Dickey Chapelle - Robuck, Erika (Sourcebook Landmark, 2025)
"Fall, 1956. Award-winning but often-maligned combat photojournalist Georgette "Dickey" Chapelle works press for the International Rescue Committee (IRC)-started by Albert Einstein during the Second World War-to bring the plight of the world's war refugees to the American people for their support. Still grieving the death of her mother, just two years after the death of her father, and in the midst of a prolonged and painful separation from her philandering husband, Dickey identifies deeply with displaced people-particularly women, children, and orphans-and longs to help them however she can. After a refugee rescue goes wrong, Dickey finds herself imprisoned in a Soviet camp, and it's there that a flame is lit deep inside her - to be the one of the front lines showing the world what war really means. Her journey will take her all over the world, and in the most perilous of dangers, Dickey will realize that in trying to galvanize the American people to save the oppressed peoples of the world, that she is saving herself"-- Provided by publisher.